Venlafaxine-induced adrenergic signaling stimulates Leydig cells steroidogenesis via Nur77 overexpression: A possible role of EGF - de Santi, Fabiane; Beltrame, Flávia L.; Rodrigues, Beatriz M. [UNESP]; Scaramele, Natália F. [UNESP]; Lopes, Flávia L. [UNESP]; Cerri, Paulo S. [UNESP]; Sasso-Cerri, Estela [UNESP] (Elsevier, 2022)
Venlafaxine, a norepinephrine and serotonin reuptake inhibitor, impairs rat sperm parameters, spermatogenesis and causes high intratesticular estrogen and testosterone levels, indicating that Leydig cells (LCs) may be a venlafaxine target. We evaluated the effect of venlafaxine treatment on rat LCs, focusing on adrenergic signaling, EGF immunoexpression and steroidogenesis. Germ cells mitotic/meiotic activity and UCHL1 levels were also evaluated in the seminiferous epithelium. Eighteen adult male rats received 30 mg/kg of venlafaxine (n = 9) or distilled water (n = 9). The seminiferous tubules, epithelium and LCs nuclear areas were measured, and the immunoexpression of Ki-67, UCHL1, StAR, EGF, c-Kit and 17β-HSD was evaluated. UCHL1, StAR and EGF protein levels and Adra1a, Nur77 and Ndrg2 expression were analyzed. Malondialdehyde (MDA) and nitrite testicular levels, and serum estrogen and testosterone levels were measured. Venlafaxine induced LCs hypertrophy and Ndrg2 upregulation in parallel to increased number of Ki-67, c-Kit- and 17β-HSD-positive interstitial cells, indicating that this antidepressant stimulates LCs lineage proliferation and differentiation. Upregulation of Adra1a and Nur77 could explain the high levels of StAR and testosterone levels, as well as aromatization. Enhanced EGF immunoexpression in LCs suggests that this growth fact is involved in adrenergically-induced steroidogenesis, likely via upregulation of Nur77. Slight tubular atrophy and weak Ki-67 immunoexpression in germ cells, in association with high UCHL1 levels, indicate that spermatogenesis is likely impaired by this enzyme under supraphysiological estrogen levels. These data corroborate the unchanged MDA and nitrite levels. Therefore, venlafaxine stimulates LCs steroidogenesis via adrenergic signaling, and EGF may be involved in this process.
Keywords: Antidepressant; EGF; Estrogen; SNRI; Spermatogenesis; UCHL1